Yanshanian deformation in Western Shandong, eastern North China Craton: Response to a transition from paleo‐Pacific to Pacific Plate subduction. (28th November 2017) - Zhang, Jian; Li, Sanzhong; Li, Xiyao; Zhao, Shujuan; Somerville, Ian D.; Li, Shaojun; Lan, Haoyuan
Abstract : The eastern part of the North China Craton has experienced cratonic destruction during the Mesozoic–Cenozoic period. However, the mechanism and geodynamic process of cratonic destruction is still not clear. The Shandong Province is a typical region that suffered the Yanshanian (Jurassic to Cretaceous) tectono‐thermal event relating to the cratonic destruction. In this paper, we focus on the Yanshanian deformation in Western Shandong and integrate the previous studies of contemporaneous magmatism. There are two‐stage compressive structures developed in Western Shandong, NE‐ or NNE‐ trending open folds, which subsequently evolved the same trend as the thrust faults. A series of NW‐trending normal faults converted from the pre‐existing Indosinian (Triassic) thrusts controlled the formation of Mesozoic basins. These deformations are a tectonic response to the subduction of the Izanagi Plate (paleo‐Pacific Plate) under the North China Craton during the Middle Jurassic and the Early Cretaceous. The Cretaceous magmatic rocks in Western Shandong mainly occurred between 130–125 Ma and have multi‐magmatic sources, including enriched lithospheric mantle, delaminated lithosphere, and subducted oceanic slab. We propose that the subduction of the Izanagi Plate converting to the Pacific Plate occurred during the middle Early Cretaceous induced a delamination of the lower crust linked to the destruction of the eastern North China Craton.